Psychological aspects of translation studies: a review of the cognitive processes involved in translation - Ziyatov, Akmal (The Lingua Spectrum, 2024)
This article explores the psychological underpinnings of the translation process, delving into the cognitive mechanisms that translators employ to decipher, interpret, and reconstruct meaning across linguistic and cultural boundaries. By examining the diverse research methodologies and theoretical frameworks employed in this field, we aim to shed light on the complex interplay between language, thought, and human cognition. The review highlights key cognitive processes, including comprehension, analysis, transfer, and synthesis, and discusses the role of individual differences, such as expertise and personality, in shaping translation outcomes. Furthermore, we consider the impact of technological advancements and the evolving landscape of translation studies on the cognitive demands placed on translators. It reviews existing research to examine how cognitive mechanisms, such as attention, memory, and problem-solving, are employed by translators to bridge linguistic and cultural gaps. By exploring these cognitive processes, the article aims to shed light on the complexities of translation and to inform future research and pedagogical practices in translation studies.